(untitled) (Journal on studies and research of academic knowledge, 2015)
The case of a patient with ectopic cervical pregnancy, who administered methotrexate intramuscularly as an alternative to surgical treatment is presented. Drug therapy consisted in the administration of methotrexate intramuscularly on alternate days, a total of 3 doses, as well as the use of folic acid by mouth in the days where methotrexate was not given. It was controlled strictly to the patient clinically, laboratory methods and ultrasound studies. The Elimination of pregnancy confirmed by anatomopathological findings obtained from a curettage evacuator.